PREDICTION BASED LOSSLESS COMPRESSION SCHEME FOR BAYER COLOUR FILTER ARRAY IMAGES USING DIFFERENT ENCODING AND DECODING TECHNIQUES - Mr. R. J. Shimpi; Prof. F. I. Shaikh (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper presents an experimental evaluation of the effectiveness of various techniques for lossless compression of CFA images. A colour image requires at least three colour samples at each pixel location. A digital camera would need three separate sensors to completely measure the image. In a three chip colour camera, the light entering the camera is split and projected onto each spectral sensor. Each sensor requires its proper driving electronics, and the sensors have to be registered precisely. These additional requirements add a large expense to the system. Thus most commercial digital cameras use colour filterarrays to sample red, green, and blue colours according to a specificpattern. At the location of each pixel only one colour sample istaken and the values of the other colours must be interpolated usingneighbouring samples.